The Effect of Volleyball Game Modifications (KASVOL) on Students' Learning Motivation in Physical Education Learning - Amansyah, Amansyah; Hardinoto, Nono (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to determine the effect of volleyball game modifications on students' learning motivation in physical education learning. The background of the research lies in the observation that conventional volleyball games often present challenges for students, such as difficulty in mastering techniques and limited involvement, which can reduce motivation. A quasi-experimental method with a pre-test-post-test control group design was used in this research. The sample consisted of 25 junior high school students divided into two groups: an experimental group that received learning through modified volleyball games and a control group that followed standard volleyball instruction. Data on learning motivation were collected through a validated questionnaire and analyzed using descriptive and inferential statistics. The results showed a significant increase in students' learning motivation in the experimental group compared to the control group. The modifications, including smaller courts, lighter balls, simplified rules, and fewer players, made the game more accessible and enjoyable, enhancing engagement and motivation. These findings suggest that volleyball game modifications (kasvol) effectively improve students' motivation in physical education learning.